Global Bollywood : travels of Hindi song and dance - Gopal, Sangita (Orient Black Swan,University of Minnesota Press, 2008)
the essays highlight the cultural influence of Hindi film music from its origins to today. Contributors: Walter Armbrust, Anustup Basu, Nilanjana Bhattacharjya, Edward K. Chan, Bettina David, Rajinder Dudrah, Shanti Kumar, Monika Mehta, Anna Morcom, Ronie Parciack, Biswarup Sen, Sangita Shrestova, Richard Zumkhawala-Cook. Re